(untitled) (Archaeologia Adriatica, 2007)
In 1999, employees of the firm Etna from Kaštel-Lukšić were quarrying within a Roman quarry on the slopes of the hill of Sv. Ilije, locally known as "Kučićeva kava", and discovered an original entrance to the quarry (Fig. 1), with several abandoned monumental stone blocks, a coarsely carved cylindrical stone vessel, probably an urn, and a very well preserved altar dedicated to Hercules, along with several characteristic amphora fragments. Although all of these finds were concealed within a several meter thick deposit of stone dust and chips, thanks to the testimony of Mr. Slavko Rodin, the owner of the firm and the quarry site, it is possible to establish with great certainty that the altar, certainly the most important find from this spot, was discovered beneath the stone cliff that overhangs the entrance to the fissure on the southern side (Fig. 2). Despite considerable damage, the altar is relatively well preserved (Fig. 3). It was made from a monolithic, vertically elongated stone block, which was divided into three sections during further work. The front side of the altar bore an inscription (Fig. 4) reading in transcription: [.]ERCVL[.] AVG . SAC . DONATVS CN . CORNELI . CERTI . V . S . L . [H]ercul[i] / aug(usto) sac(rum) / Donatus / Cn(ei) Corneli(i) / Certi (servus) v(otum) s(olvit) l(ibens). The altar was raised to Hercules by Donatus, the slave of Cneius Cornelius Certus. The lateral sides of the altar display two scenes of symbolic character. The characteristic attributes of Hercules were depicted on the left side, which even without a legend would bring to mind his heroic aspect and greatest deeds: a club, the pelt of the Nemean lion, and a branch with the golden apples of the Hesperides (Fig. 5). The right lateral side showed a tripod with a handled goblet (skyphos), the usual cult inventory of every shrine, representing equipment that the craftsman or client had personally seen and experienced (Fig. 6). The goblet has a significant place in the iconography of Hercules just like the other depicted attributes: it is a symbol of his participation at the banquets of the gods (and hence immortality), and it is a common attribute of Hercules Bibax, as well as Hercules with the incorrect epithet of Dexioumenos, Hercules offering a libation to the gods, and one of two statuary types of the drunken Hercules (staggering Hercules). The connection of Hercules to individual types of goblets is also apparent in the presence of what are known as Hercules’ knots on their handles (nodus Herculaneus/Herculeus), and according to an anonymous Athenian author from Naukratis (Athenaios), such handles were specific to vessels called Herculean goblets (Greek skifoi Herakleotikoi). For the Romans, the goblet could also have been an allusion to Hercules’ passage from Greece to the west, in the golden goblet sent to him by Helios, and his return with the cattle of Geryon through Rome and the killing of Cacus as the cause for the introduction of his cult at the Forum Boarium. It is also possible to consider certain parts of the two images on a common symbolic level: the apple branch and the goblet could also represent symbols of plenty, and hence also health, two very important aspects of the Roman Hercules. The quality of the workmanship on the altar can be evaluated as very good. Evidently the reliefs and the inscription were carved by one or several skilled stonemasons. The high quality of the sculptural work can best be seen on the scenes of the club with the lion skin and the tripod. In the first image, the back part of the lion skin was not merely shortened, but was also carved in shallow relief, which resulted in an exceptionally successful depiction of perspective. The same effect was also achieved in the scene with the tripod, where the rear leg of the table was shortened and depicted flatly. Despite such well-carved details of the relief, it is also possible to note some that are on a much lower, almost naïve level. One more detail of the workmanship of stylistic character should be noted, being the result of the use of specific stone-working tools. This is a smooth band of lesser width that can be noted at several places on the lateral sides. The stonemason, holding a toothed chisel flatly, "bordered" the surface of the relief, in this manner separating it from the otherwise somewhat more coarsely worked flat surfaces (Fig. 7). The period of carving the altar can be determined with great precision, through a comprehensive analysis of the varied content and the formal and stylistic characteristics. From parallel analysis of the fragments of the Dressel 2-4 type amphora discovered near the altar (Fig. 8), as well as the stylistic characteristics of the sculptural treatment, and particularly the analysis of the depicted skyphos, it is possible to conclude that the altar was carved during the second quarter or at latest the third quarter of the 1st century. The depicted goblet has all the characteristics of the relief skyphoi of Asia Minor: finger-shaped handles with platelets for thumbs, a garland motif, and ribbed rounding that was most probably inspired by spear-shaped leaves, behind which were the tops of tongue-shaped leaves. It can thus be hypothesized that this was the visualization of an actual form of skyphos that was in use at that time.